Flanimales pop-up - Gervais, Ricky; Steen, Rob; Fernandez, Laura (Edebé, 2010)
A field guide to a bizarre group of creatures called Flanimals showcases their many colorful varieties and their odd behavior, disgusting diet, and strange way of interacting. - A pop-up field guide to a bizarre group of creatures called Flanimals showcases their many colorful varieties and their odd behaviors, disgusting diets, and strange ways of interacting
Cover title
Keywords: Imaginary creatures / Fiction; Monsters / Fiction; Humorous stories; Monsters / Humor; English wit and humor; Animals, Mythical / Fiction; Pop-up books / Specimens; Toy and movable books / Specimens; Ungeheuer; Bilderbuch